Psychological effects of, and compliance with, self-isolation among COVID-19 patients in South Batinah Governorate, Oman: a cross-sectional study - Zayid K. Almayahi; Nasser Al Lamki (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2022)
Abstract Background Covid-19 pandemic has left deep psychological impacts, especially among infected patients. It is extremely important to understand the extent of those effects, while improving the compliance with isolation measures at the same time. Objectives To detect prevalence of stress using two psychological scales and examine the stress associated factors, also to identify self-isolation compliance rates among COVID-19 patients. Methods Cross-sectional research was conducted from 15 November to 22 December 2020, involving 379 patient participants selected via systematic random sampling. Kessler 10 Psychological Distress (K10) and the impact of event scale-revised (IES-R) tests were used to ascertain the levels of distress. Results K10 measure revealed elevated stress amongst 121 (31.9%) of participants, whereas IES_R indicated the level was 37.7%. Using the K10 indicated the multivariate analysis was significant for females (OR = 2.482, 95% CI: 1.532–4.021), patients with financial problems (OR = 2.332, 95% CI: 1.270–4.282) and patients experiencing shortages of essentials (OR = 4.920, 95% CI: 2.524–9.590). The IES-R scale indicated that only female and patients experiencing shortages scored significantly in multivariate analysis, (OR = 1.895, 95% CI: 1.1223–2.935) and (OR = 2.928, 95% CI: 1.1580–5.424), respectively. Those undergoing shorter isolation periods reported lower levels of stress on both K10, p=0.016 and IES-R, p=0.002. Approximately 90% of patients used their own towels during isolation. Moreover, 80.2% slept in separate rooms and 74% used masks in the presence of other family members. Essential supply shortages were reported by 14.2% of respondents. Conclusions Self-compliance rates were not optimal, while psychological distress was more prevalent among some groups. Intervention is imperative to minimize stress and improve self-isolation compliance.